2010
DOI: 10.1212/wnl.0b013e318200d78d
|View full text |Cite
|
Sign up to set email alerts
|

Novel CSF biomarkers for frontotemporal lobar degenerations

Abstract: Objective: To identify antemortem CSF diagnostic biomarkers that can potentially distinguish between the 2 main causes of frontotemporal lobar degeneration (FTLD), i.e., FTLD with TDP-43 pathology (FTLD-TDP) and FTLD with tau pathology (FTLD-tau).Methods: CSF samples were collected antemortem from 23 patients with FTLD with known pathology to form a autopsy cohort as part of a comparative biomarker study that additionally included 33 living cognitively normal subjects and 66 patients with autopsy-confirmed Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 37 publications
0
61
0
Order By: Relevance
“…We observed that combination of MFG‐E8 together with CSF tTau and A β 42 could discriminate FTLD patients from nondemented controls with 78% sensitivity and 82% specificity, which was validated in a larger independent cohort achieving sensitivity and specificity values >80%. Most of the potential FTLD CSF biomarkers studied to date (e.g., tau, tdp43) did not achieve enough sensitivity or specificity 8, 49, 50, 51, 52. In a subset of cases, we observed that the FTLD vs. CON model achieved similar performance to that observed for NfL alone.…”
Section: Discussionmentioning
confidence: 58%
“…We observed that combination of MFG‐E8 together with CSF tTau and A β 42 could discriminate FTLD patients from nondemented controls with 78% sensitivity and 82% specificity, which was validated in a larger independent cohort achieving sensitivity and specificity values >80%. Most of the potential FTLD CSF biomarkers studied to date (e.g., tau, tdp43) did not achieve enough sensitivity or specificity 8, 49, 50, 51, 52. In a subset of cases, we observed that the FTLD vs. CON model achieved similar performance to that observed for NfL alone.…”
Section: Discussionmentioning
confidence: 58%
“…T-tau: A␤ is not, however, sensitive for discriminating between pathologic subtypes of FTLD, and future work is required to identify candidate CSF biomarkers for further discriminating between these subgroups of FTLD. 34 We conclude that individuals with AD and FTLD have significant changes in WM and GM that appear to reflect distinct underlying neuropathologic processes with reasonably high accuracy. This multimodal approach supports noninvasive classification of individual patients with a high degree of sensitivity and specificity in a clinical setting.…”
Section: Resultsmentioning
confidence: 72%
“…In addition to increasing total food intake in rats, AgRP may also lead to a preference for fat-enriched food, 27 and sucrose in the setting of a high-fat diet. 28 One previous study 11 in FTD has suggested that elevated AgRP in CSF may be related to TDP-43 pathology, a finding likely driven by the numbers of patients with svPPA within that cohort; however, this study did not examine the relationship of this peptide to eating behavior or effect on BMI. The current study points toward an important role of AgRP in the eating abnormalities and metabolic changes 4 possibly by promoting hyperphagia, particularly affecting BMI.…”
mentioning
confidence: 85%
“…10 An approximately 7-fold increase in CSF AgRP has previously been identified in patients with FTD who have TAR DNAbinding protein 43 (TDP-43) pathology compared to those with tau pathology, an increase associated with the svPPA phenotype. 11 Changes in peripheral eating hormones have not been comprehensively investigated in svPPA, despite the increasing evidence of Figure 1 Peripheral and central pathways and the hypothalamus, controlling appetite and feeding behavior…”
mentioning
confidence: 99%